(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Datamining field that aims to bring out knowledge from three different form of Structured and unstructured, Semi structured forms. Classification techniques can be used to classify the large Volume of data and Variety of data. Classification supervised learning approach to data processing and WEKA tool is an effective and efficient tool with many inherent methods for extracting useful information. In this paper using the weka tool to analyze consumer data in the weka tool having the number of algorithm. In that algorithm we are used classification algorithm Bayes Network algorithm, Naive Bayes algorithm. Consumer behavior analysis is important of making decisions in the supermarket, consumer behavior prediction different data include in consumer behaviour analysis explains the all data and also use to identify the hidden relationships of data.